2015
DOI: 10.1111/pan.12751
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of acute severe complications of pediatric anesthesia

Abstract: The data on pediatric anesthesia acute severe complications are poorly defined with large variation in the specificity of diagnostic reporting even within studies. We suggest that it is vital for future studies in this area to be based on a standardized system of diagnostic reporting (possibly with a hierarchical system of coding) with adequate description of population details to describe heterogeneity of data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 40 publications
4
24
0
Order By: Relevance
“…Perioperative respiratory adverse events (PRAE) are the most common critical incidents encountered in paediatric anaesthesia, [1][2][3][4] and account for a third of anaesthesia-related cardiac arrests. 5 While the incidence of PRAE is 15% in a general paediatric population, the rate of PRAE is doubled in infants.…”
Section: Introductionmentioning
confidence: 99%
“…Perioperative respiratory adverse events (PRAE) are the most common critical incidents encountered in paediatric anaesthesia, [1][2][3][4] and account for a third of anaesthesia-related cardiac arrests. 5 While the incidence of PRAE is 15% in a general paediatric population, the rate of PRAE is doubled in infants.…”
Section: Introductionmentioning
confidence: 99%
“…(12,13) Our findings cannot be compared to other published studies, since this was the first time that an attempt was performed to estimate unexpected and unreported perioperative mortality through mass media report. We included all kinds of complications, both surgical and anesthesiological while other reviews and databases selectively report anesthesiological or surgical complications, (1,3,14,15) not allowing an understanding of the real overall mortality rate in the pediatric surgical setting.…”
Section: Discussionmentioning
confidence: 99%
“…(14) A recent meta-analysis of acute severe complications of pediatric anesthesia failed to find any strong data regarding mortality, underlying the fact that the majority of the studies analyzed failed to provide data. (15) Children are often scheduled together with adults on operating lists in non-pediatric hospitals, but several studies suggested that in pediatric surgery, outcomes could be associated with hospitals' operative volumes or the surgeon's experience. (16) …”
Section: Discussionmentioning
confidence: 99%
“…Adverse respiratory events are related to pediatric morbidity and mortality . Sedatives and anesthetics can depress the central nervous system, causing respiratory failure.…”
Section: Perioperative Patient Thirstmentioning
confidence: 99%